Imidazole-doped Poly(styrene sulfonic acid-co-vinyl imidazole)/Polyvinyl Alcohol Blends as Proton Conducting Membranes - Chayanan Boonrawd (Science Faculty of Chiang Mai University, 2019)
Proton-conducting membranes from imidazole-doped poly (styrene sulfonic acid-co-vinyl imidazole) (PSSA-co-PVIm)/polyvinyl alcohol (PVA) blends were reported. PSSA-co-PVIm with SSA:VIm of 5:1, 3:1, and 2:1 were synthesized via conventional free radical polymerization. Successful syntheses were confirmed by 1H-nuclear magnetic resonance spectroscopy (NMR), elemental analysis, and Fourier transform infrared spectroscopy (FTIR). The copolymers were blended with PVA and imidazole. PVA/imidazole membrane was also prepared for comparison. Hygroscopic self-standing membranes were obtained from solution-cast method. All blend membranes showed thermal decomposition onsets of 140 °C. Proton conductivity at room temperature depended highly on relative humidity. Proton conductivities of 10-3 S/cm were obtained from membranes equilibrated with water vapor, while 2-4 orders of magnitude decreases were observed for dry membranes. Under non-humidified condition, conductivity was enhanced through the addition of PSSA-co-PVIm, and maximum conductivities of 7.9 ´ 10-4 S/cm at 80-160 °C were achieved from (3:1) and (2:1) blend membranes.